Assessment practices implemented by teachers: "innovative" school vs. traditional school - Zulma Perassi (Universidad Politécnica Salesiana, 2014)
This work is framed within the research project called "Educational Assessment as a Challenge: Discourses and Practices. Subjects and contexts", which is conducted at Universidad Nacional de San Luis, Argentina. The main objective is to analyse the differences and similarities of assessment practices implemented by teachers working at "innovative" schools - Alternative Schools - and state-owned traditional schools. The study focuses on state-owned schools from the province of San Luis. The preparation of this presentation is based on investigations conducted along several years in the field of educational assessment, it deepens the approach to assessment taken at innovative schools, and it contrasts the characteristic features of both innovative and traditional educational contexts. The study adopts a qualitative paradigm, and it also resorts to observation records, production analysis, interviews, and some questionnaires. The results obtained suggest several similarities, among which the most striking one is the lack of connections between discourses and practices. A clear tendency to prioritise the assessment of processes in the context of alternative schools is observed. However, the place of the student continues to be subsidiary in both contexts. Has the innovative character of foundational projects managed to transfuse those assessment practices that are kept in those schools? Do the current ways to conceive assessment help in the formation of democratic individuals?